Research Literacy in Education and the Implementation of Evidence-Based Practices in Schools - Terje Ogden (Professions and Professionalism, 2023)
Increased focus on and interest in Evidence-Based Practices (EBP) in schools justify a stronger focus on research literacy and implementation knowledge. This article presents two complementary perspectives on the transfer of educational research to practice. The “research literacy approach” focuses on the general competence and capacity of teachers to critically assess research before it is put into practice. The “school-wide implementation approach” has a broader perspective including organizational factors and the context of teaching. A review group which examined relevant research literature on implementation in schools identified six core components that advanced EBP. An example of a school-wide implementation in Norway is presented, which illustrates how a school-wide model was put into practice based on guidelines produced by experts in the field. In conclusion, both the “research literacy” and the “whole-school” approach can advantageously strengthen their emphasis on implementation knowledge in order to promote EBP in schools.